Germline epigenetic inheritance: Challenges and opportunities for linking human paternal experience with offspring biology and health. Issue 4 (20th March 2020) - Ryan, Calen P.; Kuzawa, Christopher W.
Abstract: Recently, novel experimental approaches and molecular techniques have demonstrated that a male's experiences can be transmitted through his germline via epigenetic processes. These findings suggest that paternal exposures influence phenotypic variation in unexposed progeny–a proposal that runs counter to canonical ideas about inheritance developed during the 20th century. Nevertheless, support for paternal germline epigenetic inheritance (GEI) in nonhuman mammals continues to grow and the mechanisms underlying this phenomenon are becoming clearer. To what extent do similar processes operate in humans, and if so, what are their implications for understanding human phenotypic variation, health, and evolution? Here, we review evidence for GEI in human and nonhuman mammals and evaluate these findings in relation to historical conceptions of heredity. Drawing on epidemiological data, reproductive biology, and molecular embryology, we outline developments and opportunities for the study of GEI in human populations, emphasizing the challenges that researchers in this area still face.